Electrochemical properties of ZnO added with Zn-Al-hydrotalcites as anode materials for Zinc/Nickel alkaline secondary batteries. (1st February 2015) - Xie, Xiaoe; Yang, Zhanhong; Feng, Zhaobin; Zhang, Zheng; Huang, Jianhang
Abstract: Zn-Al layer double hydroxides (LDHs) were prepared through a simple hydrothermal method and proposed as an anode additive for Zn/Ni alkaline secondary batteries. The X-ray diffraction (XRD) and scanning electron microscopy (SEM) of sample LDHs indicates that LDHs was well prepared. The electrochemical properties of the ZnO anodes with different contents of Zn-Al-LDHs were investigated by galvanostatic charge-discharge, cyclic voltammetry (CV) and electrochemical impedance spectroscope (EIS). The structures and morphologies after cycles were also measured by SEM. The results indicate that the presence of Zn-Al-LDHs in the electrode exhibits better electrochemical performance compared with the pure ZnO electrode, such as superior electrochemical cycle stability, better reversibility and higher discharge capacity and utilization ratio. Especially for the electrode added with 24% Zn-Al-LDHs, the discharge capacity hardly declined over 250 cycles, the average utilization ratio could reach 98.5%, and the electrode had no obvious shape change and Zn dendrites after the cycling tests.